2017
DOI: 10.2147/jaa.s121092
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of asthma: utility and limitations

Abstract: Clinical studies in asthma are not able to clear up all aspects of disease pathophysiology. Animal models have been developed to better understand these mechanisms and to evaluate both safety and efficacy of therapies before starting clinical trials. Several species of animals have been used in experimental models of asthma, such as Drosophila, rats, guinea pigs, cats, dogs, pigs, primates and equines. However, the most common species studied in the last two decades is mice, particularly BALB/c. Animal models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(146 citation statements)
references
References 92 publications
2
137
0
4
Order By: Relevance
“…Numerous animal models have been used to decipher various aspects of asthma pathophysiology, identify novel therapeutic targets, and test the efficacy of emerging therapies. Reports using models of Drosophila melanogaster (Roeder et al, 2009), canines (Padrid, 1992;Zosky and Sly, 2007), felines (Norris Reinero et al, 2004), rats (Kucharewicz et al, 2008), equines (Herszberg et al, 2006), sheep (Zosky and Sly, 2007;Scheerlinck et al, 2008), guinea pigs (Canning and Chou, 2008), nonhuman primates (Coffman and Hessel, 2005), and mice (Zosky and Sly, 2007;Nials and Uddin, 2008;Chapman et al, 2014;Aun et al, 2017) can be found in the literature. Although felines and equines spontaneously display asthma-like symptoms, 1% of cats develop eosinophilic bronchitis (Padrid, 2000;Aun et al, 2017), and horses develop heaves resulting from moldy hay (Barton and Gehlen, 2016); they are not financially viable models for asthma research.…”
Section: Preclinical Models Of Asthmamentioning
confidence: 99%
“…Numerous animal models have been used to decipher various aspects of asthma pathophysiology, identify novel therapeutic targets, and test the efficacy of emerging therapies. Reports using models of Drosophila melanogaster (Roeder et al, 2009), canines (Padrid, 1992;Zosky and Sly, 2007), felines (Norris Reinero et al, 2004), rats (Kucharewicz et al, 2008), equines (Herszberg et al, 2006), sheep (Zosky and Sly, 2007;Scheerlinck et al, 2008), guinea pigs (Canning and Chou, 2008), nonhuman primates (Coffman and Hessel, 2005), and mice (Zosky and Sly, 2007;Nials and Uddin, 2008;Chapman et al, 2014;Aun et al, 2017) can be found in the literature. Although felines and equines spontaneously display asthma-like symptoms, 1% of cats develop eosinophilic bronchitis (Padrid, 2000;Aun et al, 2017), and horses develop heaves resulting from moldy hay (Barton and Gehlen, 2016); they are not financially viable models for asthma research.…”
Section: Preclinical Models Of Asthmamentioning
confidence: 99%
“…In addition, the importance of obesity, age (neonatal and aged mice) and the microbiome in asthma onset and progression should be taken into account (table 9) [104,105]. The advantages and disadvantages of specific animal species in experimental models of asthma should be considered [106]; e.g. for investigating early and late asthmatic responses, neuronal aspects and cough, including activity of β2-bronchodilators and pharmacological studies, research in the guinea pig can provide important insights [107][108][109].…”
Section: How Can We Model Specific Clinically Relevant Phenotypes/endmentioning
confidence: 99%
“…Smoking cessation is the most effective means for reducing disease progression, although, many smokers with COPD are undiagnosed and thus unaware that their habit is harming them drastically (28). Once a patient is diagnosed with COPD, treatment is based on the progression of the disease state as determined by spirometry and whether the symptoms are intermittent or persistent ( (110). Asthma is not a murine disease and thus mice must become sensitized to increase allergen immunogenicity, which is followed by an allergen challenge (110).…”
Section: Managementmentioning
confidence: 99%
“…Once a patient is diagnosed with COPD, treatment is based on the progression of the disease state as determined by spirometry and whether the symptoms are intermittent or persistent ( (110). Asthma is not a murine disease and thus mice must become sensitized to increase allergen immunogenicity, which is followed by an allergen challenge (110).…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation